Corporate governance in major South African state-owned enterprises - Ngwenya, Bongani (My University, 2018)
ABSTRACT As a result of SOEs continued dependence on government bailouts and everincreasing embroilment in corruption scandals this study aims to establish the nature of the relationship that certain corporate governance related characteristics have on the performance of major SOEs in South Africa. Schedule 2 of the PFMA lists the 21 firms considered to be major public SOEs in South Africa. This list formed the basis for the SOE’s that were included in the study. A study of the relevant literature was used to determine the appropriate governance and performance metrics before data was then collected from publicly available sources on these metrics. The data collected was then used to perform a regression analysis in order to explore the relationship between governance and performance. It is found that there is a significant negative relationship between the number of board meetings held and SOE performance. Secondly, female representation on the board has a direct and positive influence on the after-tax profits of an SOE. Thirdly, SOEs with higher paid CEOs produced higher after-tax profits than those with lower paid CEOs. Finally, CEOs with tenure of less than a year are able to deliver performance gains over their longer tenured counterparts.
Keywords: Corporations -- South Africa. Corporate governance -- South Africa.